CYP2D6 genotyping in the daily routine of a psychiatric hospital – pharmacoeconomic evaluation - A. A. Kurylev; B. V. Andreev; A. S. Kolbin; O. V. Limankin (Фармакоэкономика)
Today, pharmacogenetic tests are commonly used to improve the efficacy and safety of antipsychotic (AP) treatment. However, the economic aspects of their implementation in the psychiatry clinic routine are not well studied.Aim.To evaluate the pharmacoeconomic benefits of CYP2D6 polymorphisms genotyping in psychiatric patients.Materials and methods. CYP2D6 genetic polymorphisms (*3, *4, *5, *6, *1ХN) were tested in  298 psychiatric in-patients. The mean AP daily doses and the hospital stay duration differed  between poor (PM), extensive (EM) and ulta-rapid (UM) metabolizers. Based on these data, a  pharmacoeconomic decision-making model was created. The model calculates direct medical costs for the patient care with and without pharmacogenetics tests.Results. Pharmacogenetics tests (CYP2D6 genotyping) performed prior to the antipsychotic  therapy were shown to be a cost-effective strategy as it gives additional clinical and  pharmacological information, optimize the duration of AP treatment, and results in a lower direct  medical cost of in-patient care. The cost of genotyping is less than 1% of the total direct medical  costs. This strategy remains cost-effective even if the genotyping costs more than 3893.8 RUB  (199% of the current value) and also if the differences in the hospital stay durations between PM, EM and UM are not less than 5 days.